The Impact of Environmental Factors on Malaria Prevalence in a Peri-Urban Community in Kwara State, Nigeria - Olubunmi Ajike Mokuolu; Oluwayemisi D Adegboye; Olugbenga A Mokuolu (International Journal of Public Health Science (IJPHS), 2014)
There is a consensus on the relationship between Malaria Prevalence (MP) and Environmental Factors (EF); however, there is a dearth of published data providing this evidence in a quantifiable way. This community based study was undertaken to identify the magnitude of the relationship between MP and key environmental factors in Okelele, Ilorin East Local Government Area of Kwara State, Nigeria. A multi-staged sampling procedure was adopted for the selection of 501 children from 200 households. Children under the age of 14 years in the selected households were sampled to obtain baseline MP using malaria Rapid Diagnostic Test (mRDT) kit. Key household informant interviews and structured questionnaire were used. Relevant socio-demographic characteristics of the households, EF and non EF were determined. Acquired data was analyzed using statistical tools to determine the relationship between various independent variables and mRDT. Variables were also entered into a multiple regression equation for the generation of a mathematical model. Ethical consent was obtained from the parents before samples were taken.The study showed that EF contributed to MP in the study area.  Integrated waste management system, and regular environmental sanitation were recommended.